2011
DOI: 10.1093/ndt/gfr618
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin ameliorates salt-sensitive hypertension and renal fibrosis

Abstract: The results suggested that RLX converted salt sensitivity to salt resistance, at least in part, by up-regulating NOS. RLX is a potentially useful therapeutic agent for salt-sensitive hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 40 publications
(49 reference statements)
4
40
1
Order By: Relevance
“…RLX may protect preservation of tubular cells and these functions by anti-apoptotic effects. Previously, we demonstrated that RXFP1 and nNOS were localized to distal tubular epithelial cells in the rats [8]. In this study, CDDP induced renal tubular injury and decreased RXFP1 and nNOS mRNA expression, whereas RLX attenuated the decrease of RXFP1 and nNOS mRNA expression by CDDP.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…RLX may protect preservation of tubular cells and these functions by anti-apoptotic effects. Previously, we demonstrated that RXFP1 and nNOS were localized to distal tubular epithelial cells in the rats [8]. In this study, CDDP induced renal tubular injury and decreased RXFP1 and nNOS mRNA expression, whereas RLX attenuated the decrease of RXFP1 and nNOS mRNA expression by CDDP.…”
Section: Discussionsupporting
confidence: 47%
“…In the short-term experiments, the paraffin-embedded kidney sections (3 μm) were stained using the periodic acid-Schiff (PAS) method. Tubular epithelial damage was evaluated using a semiquantitative grading system as described previously [8]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining Dahl salt-sensitive hypertensive with Dahl saltresistant normotensive rats, researchers in Japan have found that when treated with H2 relaxin after six weeks, 34) DS rats' systolic blood pressure decreased significantly, glomerular and tubular fibrosis lesions were alleviated and TGF-β signal transduction decreased. In another study, 35) administration of H2 relaxin to rats with the anti-thymocyte serum nephritis model resulted in a decrease of PAS staining positive matrix, SMAD2 phosphorylation and mesangial cell proliferation while α-SMA expression were found.…”
Section: Discussionmentioning
confidence: 99%